2020
DOI: 10.1016/j.omtm.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Intralingual and Intrapleural AAV Gene Therapy Prolongs Survival in a SOD1 ALS Mouse Model

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that results in death from respiratory failure. No cure exists for this devastating disease, but therapy that directly targets the respiratory system has the potential to prolong survival and improve quality of life in some cases of ALS. The objective of this study was to enhance breathing and prolong survival by suppressing superoxide dismutase 1 (SOD1) expression in respiratory motor neurons using adeno-associated virus (AAV) expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…Indeed, differences between fast and slow IT injection of viral vector in SOD1-G93A mice were analysed and it was demonstrated that the slower one enhances transduction of spinal cord and therapeutic efficacy [ 85 ]. Alternative delivery routes of administration are also investigated, such as a combination of intralingual and intrapleural injections [ 86 ].…”
Section: Aav-mediated Silencing Approaches For Fals (Sod1 and C9orf72mentioning
confidence: 99%
“…Indeed, differences between fast and slow IT injection of viral vector in SOD1-G93A mice were analysed and it was demonstrated that the slower one enhances transduction of spinal cord and therapeutic efficacy [ 85 ]. Alternative delivery routes of administration are also investigated, such as a combination of intralingual and intrapleural injections [ 86 ].…”
Section: Aav-mediated Silencing Approaches For Fals (Sod1 and C9orf72mentioning
confidence: 99%
“…Intralingual vector delivery effectively drives gene and protein expression in the tongue [32,[45][46][47] and can reverse tongue muscle histopathology in neuromuscular disease [45][46][47]. Pompe disease is a neuromuscular disorder associated with mutations in a single gene (acid alpha glucosidase or GAA), macroglossia, dysphagia, and dysarthria [48].…”
Section: Targeting the Tongue Via Intralingual Viral Deliverymentioning
confidence: 99%
“…Furthermore, treatment delayed weight loss and limb weakness. Despite the therapy succeeding in improving breathing and survival, it failed to amend the restrictive lung phenotype [ 110 ]. Although we consider the AAV with artificial miRNAs targeting SOD1 systems to show promising outcomes, we need to keep track of it for the next few years.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%